The Coenzyme Q10 Production from Rhodopseudomonas sp. S12-13 Mutant - Krairak, Somchai; Krairak, Nisa (Burapha Science Journal, 2026)
Rhodopseudomonas sp. S12-13 was retrieved from the mutation of the wild type, Rhodopseudomonas S12, by UV-irradiation. The mutant, S12-13 contained the cassava starch digestibility resulting in the high amount of coenzyme Q10 production at 148.12±21.74 µg/L when cultivating in AM medium containing of 2% cassava starch and 1% glutamate as carbon and nitrogen sources, respectively. In case of wild type, S12, the coenzyme Q10 production was only 12.51±1.34 µg/L when cultivating in AM medium. Mutant S12-13 produced maximal coenzyme Q10 (186.91±28.97 µg/L), when it was cultivated in the rectangle bottle, that contained 200 cm2 of light exposure surface area. For the cultivation in cylindrical bottle, which contained 143 cm2 of light exposure surface area, one would produce 151.70±21.64 µg/L of coenzyme Q10.